The Underlying molecular mechanism of bufei yishen prescription for copd in mice model based on NFR1/PPAR γ pathway - Xu, Cong (2024)
Chronic Obstructive Pulmonary Disease (COPD) is a debilitating respiratory disorder characterized by persistent airflow limitation and oxidative stress-induced inflammation. Bufei Yishen Prescription (BYP), a traditional Chinese medicine formula, has shown promising therapeutic effects on COPD. However, the precise molecular mechanisms underlying its efficacy remain unclear. This study investigates the potential therapeutic mechanisms of BYP in a COPD mice model, focusing on the NRF2/PPARγ signaling pathway. Using a murine model of COPD induced by cigarette smoke exposure, we found that Bufei Yishen prescription can effectively improve the general condition, lung function and lung tissue injury of COPD mice model, reduce the expression level of pulmonary inflammatory factors, improve the efferocytosis function of alveolar macrophages in COPD mice model, reduce the apoptosis rate of lung tissue, and inhibit the number and polarization of macrophages. In conclusion, our study elucidates the molecular mechanisms underlying the therapeutic effects of Bufei Yishen Prescription in a COPD mice model. BYP exerts its beneficial effects by activating the NRF2/PPARγ pathway, leading to enhanced antioxidant defense and reduced inflammation. These findings provide valuable insights into the potential of BYP as a complementary therapeutic approach for COPD and underscore the importance of NRF2/PPARγ signaling in COPD pathogenesis. Further clinical studies are warranted to validate these findings and explore the translational potential of BYP in COPD management. Key Words Chronic obstructive pulmonary disease, alveolar macrophages, efferocytosis, PPARγ, Nrf2, Bufei Yishen Prescription